Gender Equality in Indonesian Employment: Multivariate Adaptive Regression Spline (Mars) Analysis - Dita Amelia; Toha Saifudin; Suliyanto Suliyanto; Aditya Syarifudin Akbar; Muhammad Rosyid Ridho Az Zuhro (Jurnal Ilmu Sosial dan Humaniora, 2024)
Based on data from the Central Bureau of Statistics, laborers in Indonesia, men are still more dominant for a career in the world of work. This contradicts the prevailing regulations, where gender equality is also a government development priority in realizing equitable development. This study aims to identify the factors that influence the percentage of women who work in Indonesia. The Multivariate Adaptive Regression Spline (MARS) Method is suitable for extensive data and can model relationships of interactions between various variables. The variables analyzed were the average wage of female workers, gross regional domestic product at constant prices, female workers with at least a high school education, life expectancy, provincial minimum wage, and female workers who are heads of households. Based on the research results, the best model was obtained with a coefficient of determination of 90.8%. Some influential variables in the base function are Minimum Wage for Female Workers, Female Workers with at least a high school education, Life Expectancy, and Female Workers who are Heads of Families. Based on the significant basis functions, the function that appears the most is Basis Function 5, which contains the predictor variable Average Wage of Female Workers, which shows a positive relationship with the Percentage of Female Workers with Labor Status in Indonesia. Meanwhile, based on the importance of the predictor variables, the top two are Female Workers with at least a high school education and Female Workers who are Heads of Households.